A battery gauze layer paper for gas stove and a preparation method thereof

By introducing a composite coating layer of modified starch and functional triaryl triazine microspheres into the slurry paper of the gas stove battery, the problem of easy corrosion of the slurry paper at high temperatures is solved, and the battery's anti-leakage, flame retardant and high temperature resistance performance is improved, ensuring the safe use of the gas stove.

CN120738949BActive Publication Date: 2025-11-21LIAOYUAN JINYU JOURNEY DIAPHRAGM CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511180512.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-22
Publication Date
2025-11-21
Estimated Expiration
2045-08-22

AI Technical Summary

Technical Problem

The pulp paper of existing carbon zinc-manganese batteries used in gas stoves is prone to corrosion under high temperature and open flame conditions, leading to electrolyte leakage and posing a safety hazard. Furthermore, it fails to simultaneously meet the requirements of excellent corrosion inhibition, flame retardancy, and high temperature resistance.

Method used

A coating layer composed of modified polyvinyl alcohol, modified starch, functional triaryl triazine microspheres, and chloroplatinic acid is used to form a composite slurry on the base paper. The coating layer contains the bisH-pyrazole methylamine ligand structure and siloxane structure on the modified starch, combined with the quaternary ammonium salt structure of the functional triaryl triazine microspheres, which enhances the protection of the zinc anode and the flame retardant and high temperature resistance of the slurry paper.

Benefits of technology

It significantly improves the leak-proof capability of gas stove batteries, enhances the flame retardancy and high-temperature resistance of the pulp paper, and ensures the safety and stability of the batteries in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120738949B_ABST
    Figure CN120738949B_ABST
Patent Text Reader

Abstract

The application discloses a kind of gas stove battery pulp layer paper and preparation method thereof, it is related to pulp layer paper technical field.The application grafts copolymerization when preparing gas stove battery pulp layer paper, and modified starch is prepared to double H-pyrazole methyl amine ligand, 1-vinyl-1,1,3,3-tetramethyl disiloxane on starch;Modified polyvinyl alcohol is prepared by the reaction of polyvinyl alcohol and 3-butene phosphonic acid monomethyl ester;Functional triaryls-triazine microspheres are prepared by the reaction of triaryl-triazine microspheres and 3-mercapto-N,N,N-trimethyl propane-1-ammonium chloride;Modified polyvinyl alcohol, modified starch, polyacrylamide, functional triaryls-triazine microspheres and chloroplatinic acid are prepared into composite slurry;Composite slurry is coated on base paper, dried, slitting, rewound to prepare gas stove battery pulp layer paper.The gas stove battery pulp layer paper prepared by the application has excellent high-temperature resistance, leakage prevention, flame retardant and mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of pulp layer paper, in particular to a gas stove battery pulp layer paper and a preparation method thereof. BACKGROUND

[0002] The battery of the gas stove is mainly used for supplying power for the electronic ignition system to ensure that the gas stove can normally ignite and ignite the gas. The carbon zinc manganese battery has low price and simple production process, and shows better stability than alkaline battery under low temperature condition, and is widely used in household appliances. For example, No. 1 carbon battery produced by Norel company, No. 1 carbon battery produced by Toshiba company, No. 1 carbon battery produced by Shuanglu company and No. 1 carbon battery produced by Changhong company can be used for household appliances such as gas stove and water heater.

[0003] The carbon zinc manganese battery is composed of positive electrode, negative electrode, electrolyte and diaphragm material; the zinc cylinder of the carbon zinc manganese battery is not only the negative active material, but also the battery shell, which directly contacts with the electrolyte and is easily corroded and perforated after long-term use, causing the leakage of the battery electrolyte. For the gas stove battery under the condition of high temperature and open flame, the leakage of the electrolyte will bring great safety hazard.

[0004] The diaphragm material of the carbon zinc manganese battery is also called pulp layer paper, which plays a role in isolating the positive and negative electrodes to prevent short circuit. In the battery, the pulp layer paper is closely attached to the inner wall of the zinc cylinder. It has been found that adding corrosion inhibitor to the pulp layer paper can inhibit the corrosion of the zinc negative electrode and improve the anti-leakage performance of the battery. However, for the carbon zinc manganese battery used in gas stove, the pulp layer paper not only needs to have excellent corrosion inhibition and leakage prevention performance, but also needs to have excellent flame retardance and high temperature resistance to meet the safety requirements. SUMMARY

[0005] The present application aims to provide a gas stove battery pulp layer paper and a preparation method thereof to solve the problems in the prior art.

[0006] In order to solve the above technical problems, the present application provides the following technical scheme:

[0007] A gas stove battery pulp layer paper, comprising a base paper and a coating layer coated on the base paper;

[0008] The coating layer is composed of 17-18 parts of modified polyvinyl alcohol, 48-50 parts of modified starch, 6-7 parts of polyacrylamide, 7-8 parts of functional triaryliminiazine microspheres and 1-1.5 parts of chloroplatinic acid;

[0009] The modified polyvinyl alcohol is prepared by reacting polyvinyl alcohol and 3-butene phosphonic acid monomethyl ester;

[0010] The modified starch is prepared by graft copolymerization of a bis-H-pyrazole methylamine ligand and 1-vinyl-1,1,3,3-tetramethyldisiloxane on starch;

[0011] The bis-H-pyrazole methylamine ligand is prepared by reaction of 4-allyl aniline and 1-pyrazole methanol;

[0012] The functional triarylimidazole microspheres are prepared by reaction of triarylimidazole microspheres and 3-mercapto-N,N,N-trimethylpropane-1-ammonium chloride;

[0013] The triarylimidazole microspheres are prepared by reaction of 2,4,6-tris(4-fluorophenyl)-1,3,5-triazine and quercitol.

[0014] A preparation method of a gas stove battery ply paper, the preparation method of the gas stove battery ply paper comprises the following preparation steps:

[0015] (1) uniformly mix a bis-H-pyrazole methylamine ligand, 1-vinyl-1,1,3,3-tetramethyldisiloxane, dodecylphenol polyoxyethylene ether, sodium dodecyl sulfate and distilled water in a mass ratio of 1:1:(3-4):(2-3):(12-14), stir at 500-600 r / min at room temperature for 20-30 min to prepare a mixed reaction solution; uniformly mix starch and distilled water in a mass ratio of 1:(20-22), stir at 76-80°C under nitrogen protection at 200-300 r / min for 30-40 min, cool to 40°C, add 0.1-0.12 times the mass of the starch of ammonium persulfate and 0.1-0.12 times the mass of the starch of sodium bisulfite, continue to stir for 10-14 min, uniformly drop the mixed reaction solution at a rate of 13-15 times the mass of the starch within 20 min, continue to stir for 5-6 h after the dropping is completed, remove the solvent by rotary evaporation under reduced pressure, wash with anhydrous ethanol and distilled water for 3-5 times, and dry at 50-60°C under vacuum for 10-12 h to prepare a modified starch;

[0016] (2) uniformly mix polyvinyl alcohol, urea, dicyandiamide and N,N-dimethylformamide in a mass ratio of 1:(2.4-2.5):(1.5-1.6):(8-9), heat to 130°C at a temperature increasing rate of 5°C / min under stirring at 200-300 r / min, add 1.2-1.3 times the mass of the polyvinyl alcohol of 3-butene phosphonic acid monomethyl ester, stir at 130-135°C for 3-4 h, dissolve the product in distilled water, precipitate with ethanol, repeat the dissolution-precipitation process for 4-6 times, and dry at 50-60°C under vacuum for 10-12 h to prepare a modified polyvinyl alcohol;

[0017] (3) triaryls-triazine microspheres, 3-mercapto-N, N, N-trimethylpropane-1- ammonium chloride, azobisisobutyronitrile, N, N-dimethylformamide are mixed uniformly in a mass ratio of 1: (3-4): (0.05-0.07): (24-26), and stirred at 70-80℃ and 300-400r / min for 6-7h, then filtered, washed with anhydrous ethanol for 3-5 times, and dried at 50-60℃ under vacuum for 10-12h to obtain functional triaryls-triazine microspheres;

[0018] (4) modified polyvinyl alcohol, modified starch, polyacrylamide, functional triaryls-triazine microspheres, chloroplatinic acid are added to distilled water and mixed uniformly, and the viscosity is adjusted to 190-200mm / s with distilled water to obtain a composite slurry; the composite slurry is uniformly coated on base paper at a coating amount of 30g / m 2 , and after coating, it is placed at 70-75℃ for 2-3h, dried at 50-60℃ under vacuum for 16-18h, cut and rewound to obtain a gas stove battery pulp layer paper. 2

[0019] As an optimization, the preparation method of the double H-pyrazole methylamine ligand in step (1) is as follows: 4-allyl aniline and 1-pyrazole methanol are added to N-methyl pyrrolidone with a mass of 4-allyl aniline of 14-16 times, and tris (triphenylphosphine) ruthenium dichloride with a mass of 4-allyl aniline of 0.06-0.08 times, and stirred at 180-190℃ and 200-300r / min for 20-24h, and dried at 50-60℃ under vacuum for 10-12h to obtain the double H-pyrazole methylamine ligand; the reaction process is as follows:

[0020] .

[0021] As an optimization, the type of polyvinyl alcohol in step (2) is PVA1788.

[0022] As an optimization, the CAS number of 3-butene phosphonic acid monomethyl ester in step (2) is 205644-49-1.

[0023] The structural formula is: .

[0024] ​As optimization, the preparation method of the triaryltriazine microspheres in step (3) is as follows: 2,4,6-tris(4-fluorophenyl)-1,3,5-triazine, quinone, anhydrous potassium carbonate are added into N-methylpyrrolidone in a mass ratio of 1:(0.8~0.9):(0.5~0.6), and the N-methylpyrrolidone is 20~24 times the mass of 2,4,6-tris(4-fluorophenyl)-1,3,5-triazine, and the toluene is 16~18 times the mass of 2,4,6-tris(4-fluorophenyl)-1,3,5-triazine, under the protection of nitrogen, under the condition of stirring at 200~300r / min at 140~150℃, refluxing for 3~4h, evaporating toluene by heating to 160℃, continuing to stir and react for 6~7h by heating to 180~190℃, cooling to room temperature, standing for 8~10h, centrifuging, washing 3~5 times with anhydrous ethanol, and drying under vacuum at-80℃ for 26~30h, to obtain the triaryltriazine microspheres.

[0025] As optimization, the CAS number of the 2,4,6-tris(4-fluorophenyl)-1,3,5-triazine is 130156-10-4.

[0026] The structural formula is: .

[0027] As optimization, the amount of the modified polyvinyl alcohol, the modified starch, the polyacrylamide, the functional triaryltriazine microspheres, and the chloroplatinic acid in step (4) is as follows: the modified polyvinyl alcohol is 17~18 parts, the modified starch is 48~50 parts, the polyacrylamide is 6~7 parts, the functional triaryltriazine microspheres are 7~8 parts, and the chloroplatinic acid is 1~1.5 parts.

[0028] As optimization, the polyacrylamide in step (4) is purchased from Shanghai Aladdin, and the article number is P434411.

[0029] Compared with the prior art, the present application has the following beneficial effects:

[0030] The application is used for preparing the battery pulp layer paper of gas stove, first, the double H-pyrazole methyl amine ligand is prepared by the reaction of 4-allyl aniline and 1-pyrazole methanol; the modified starch is prepared by the graft copolymerization of the double H-pyrazole methyl amine ligand and 1-vinyl-1,1,3,3-tetramethyl disiloxane on the starch; the double H-pyrazole methyl amine ligand structure, siloxane structure and Si-H are introduced on the modified starch; the double H-pyrazole methyl amine ligand structure has strong coordination ability, can be complexed with zinc ions on the surface of zinc negative electrode, forms a protective layer, prevents the further corrosion of the zinc negative electrode, and improves the leakage prevention performance of the battery; the introduction of the siloxane structure can improve the flame retardation and high temperature resistance of the pulp layer paper; the Si-H introduced on the modified starch can occur the silicon hydrogen addition reaction with the carbon-carbon double bond introduced on the side chain of the modified polyvinyl alcohol molecule, forms a crosslinking structure, the three-dimensional network structure formed by the crosslinking reaction limits the movement between the molecular chains, reduces the thermal degradation under high temperature, and further improves the high temperature resistance and mechanical strength.

[0031] Secondly, the modified polyvinyl alcohol is prepared by the reaction of polyvinyl alcohol and 3-butene phosphonic acid monomethyl ester; the esterification reaction occurs between the part of hydroxyl groups on the side chain of the polyvinyl alcohol molecule and the phosphoric acid group of 3-butene phosphonic acid monomethyl ester, the phosphorus element and carbon-carbon double bond are introduced on the side chain of the modified polyvinyl alcohol molecule, and the introduction of the phosphorus element further improves the flame retardation of the pulp layer paper.

[0032] Finally, the triaryl s-triazine microspheres are prepared by the reaction of 2,4,6-tris(4-fluorophenyl)-1,3,5-triazine and phragmites communis phenol, and the carbon-carbon double bond is introduced on the triaryl s-triazine microspheres; the functional triaryl s-triazine microspheres are prepared by the reaction of the carbon-carbon double bond on the triaryl s-triazine microspheres and the mercapto group on 3-mercapto-N,N,N-trimethylpropane-1-ammonium chloride; the quaternary ammonium salt structure is grafted on the surface of the functional triaryl s-triazine microspheres; the positively charged quaternary ammonium salt structure can occur the positive and negative charge combination with the negatively charged zinc surface after corrosion, is adsorbed on the surface of the zinc negative electrode, delays the further corrosion of the zinc surface, and thus improves the leakage prevention performance of the battery; meanwhile, the functional triaryl s-triazine microspheres contain the triaryl s-triazine structure, have excellent flame retardation and high temperature resistance, and can further improve the flame retardation and high temperature resistance of the pulp layer paper. BRIEF DESCRIPTION OF DRAWINGS

[0033] Figure 1 It is the leakage effect comparison chart of example 1 and comparative example 1; the left side is comparative example 1, and the right side is example 1;

[0034] Figure 2 It is the thermal gravimetric analysis chart of example 2 and comparative examples 1-4. DETAILED DESCRIPTION

[0035] With reference to the embodiments of the present application, the technical solutions in the embodiments of the present application will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments of the present application, all the other embodiments obtained by a person of ordinary skill in the art without creative effort belong to the protection scope of the present application.

[0036] Embodiment 1: A preparation method of a gas stove battery ply paper, the preparation method of the gas stove battery ply paper comprises the following preparation steps:

[0037] (1) 4-allyl aniline, 1-pyrazole methanol are added into N-methyl pyrrolidone with a mass of 14 times of 4-allyl aniline at a molar ratio of 1:2, and tris(triphenylphosphine)ruthenium dichloride with a mass of 0.06 times of 4-allyl aniline is added, stirring at 180 ℃ and 200 r / min for 24 h, and drying at 50 ℃ under vacuum for 12 h to obtain a double H-pyrazole methyl amine ligand; the double H-pyrazole methyl amine ligand, 1-vinyl-1,1,3,3-tetramethyldisiloxane, dodecylphenol polyoxyethylene ether, sodium dodecyl sulfate and distilled water are uniformly mixed at a mass ratio of 1:1:3:2:12, and stirred at room temperature and 500 r / min for 30 min to prepare a mixed reaction solution; starch and distilled water are uniformly mixed at a mass ratio of 1:20, stirring at 76 ℃ and 200 r / min for 40 min under nitrogen protection, the temperature is reduced to 40 ℃, ammonium persulfate with a mass of 0.1 times of the starch is added, sodium bisulfite with a mass of 0.1 times of the starch is added, and stirring is continued for 14 min, the mixed reaction solution with a mass of 13 times of the starch is added at a uniform speed within 20 min, and after the addition is completed, the reaction is continued for 6 h, the solvent is removed by rotary evaporation under reduced pressure, and the modified starch is obtained by washing with anhydrous ethanol and distilled water for 3 times and drying at 50 ℃ under vacuum for 12 h;

[0038] (2) polyvinyl alcohol, urea, dicyandiamide and N,N-dimethylformamide are uniformly mixed at a mass ratio of 1:2.4:1.5:8, and heated to 130 ℃ at a temperature increasing rate of 5 ℃ / min under the condition of stirring at 200 r / min, 3-butenephosphonic acid monomethyl ester with a mass of 1.2 times of the polyvinyl alcohol is added, and stirring reaction is carried out at 130 ℃ for 4 h, the product is dissolved in distilled water, precipitated with ethanol, and the dissolution-precipitation process is repeated for 4 times, and the modified polyvinyl alcohol is obtained by drying at 50 ℃ under vacuum for 12 h;

[0039] (3) 2,4,6-tris(4-fluorophenyl)-1,3,5-triazine, quinone, anhydrous potassium carbonate are added into N-methylpyrrolidone with 20 times of the mass of 2,4,6-tris(4-fluorophenyl)-1,3,5-triazine, and added into toluene with 16 times of the mass of 2,4,6-tris(4-fluorophenyl)-1,3,5-triazine, under the protection of nitrogen, under the condition of stirring at 200 r / min at 140℃, refluxing for 4h, increasing the temperature to 160℃ to distill toluene, increasing the temperature to 180℃, continuing to stir for 7h, cooling to room temperature, standing for 8h, centrifuging, washing with anhydrous ethanol for 3 times, drying at -80℃ under vacuum for 26h, to obtain triaryltriazine microspheres; the triaryltriazine microspheres, 3-mercapto-N,N,N-trimethylpropane-1-aminium chloride, azobisisobutyronitrile, N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:3:0.05:24, stirring at 70℃ at 300 r / min for 7h, suction filtration, washing with anhydrous ethanol for 3 times, drying at 50℃ under vacuum for 12h, to obtain functional triaryltriazine microspheres;

[0040] (4) 17 parts of modified polyvinyl alcohol, 48 parts of modified starch, 6 parts of polyacrylamide, 7 parts of functional triaryltriazine microspheres, and 1 part of chloroplatinic acid are weighed according to the mass fraction; the modified polyvinyl alcohol, the modified starch, the polyacrylamide, the functional triaryltriazine microspheres, and the chloroplatinic acid are added into distilled water and mixed uniformly, and the viscosity is adjusted to 190mm 2 / s with distilled water, to obtain a composite slurry; the composite slurry is uniformly coated on base paper, the coating amount is 30g / m 2 , after coating, standing at 70℃ for 3h, drying at 50℃ under vacuum for 18h, slitting and rewinding, to obtain a gas stove battery pulp layer paper.

[0041] Example 2: a preparation method of a gas stove battery pulp layer paper, the preparation method of the gas stove battery pulp layer paper comprises the following preparation steps:

[0042] (1) 4-allyl aniline, 1-pyrazole methanol are added into N-methyl pyrrolidone with 15 times of the mass of 4-allyl aniline according to a molar ratio of 1:2, and 4-allyl aniline 0.07 times of the mass of tris(triphenylphosphine) ruthenium dichloride is added, stirring at 185℃, 250r / min for 22h, and drying under vacuum condition at 55℃ for 11h to prepare a double H-pyrazole methyl amine ligand; the double H-pyrazole methyl amine ligand, 1-vinyl-1,1,3,3-tetramethyldisiloxane, dodecylphenol polyoxyethylene ether, sodium dodecyl sulfate, distilled water are mixed uniformly according to a mass ratio of 1:1:3.5:2.5:13, and stirred at room temperature, 550r / min for 25min to prepare a mixed reaction liquid; starch and distilled water are mixed uniformly according to a mass ratio of 1:21, and stirred at 78℃ under nitrogen protection, 250r / min for 35min, and then cooled to 40℃, and 0.11 times of the mass of starch ammonium persulfate and 0.11 times of the mass of starch sodium bisulfite are added, and stirring is continued for 12min, and the mixed reaction liquid with 14 times of the mass of starch is added at a uniform speed within 20min, and after the addition is completed, stirring reaction is continued for 5.5h, and the solvent is removed by rotary evaporation under reduced pressure, and washed with anhydrous ethanol and distilled water for 4 times respectively, and dried under vacuum condition at 55℃ for 11h to prepare a modified starch;

[0043] (2) polyvinyl alcohol, urea, dicyandiamide, N,N-dimethylformamide are mixed uniformly according to a mass ratio of 1:2.45:1.55:8.5, and heated to 130℃ at a heating rate of 5℃ / min under stirring condition at 250r / min, and 1.25 times of the mass of polyvinyl alcohol 3-butene phosphonic acid monomethyl ester is added, and stirring reaction is carried out at 132.5℃ for 3.5h, and the product is dissolved in distilled water, and then precipitated with ethanol, and the dissolution-precipitation process is repeated for 5 times, and dried under vacuum condition at 55℃ for 11h to prepare a modified polyvinyl alcohol;

[0044] (3) 2,4,6-tris(4-fluorophenyl)-1,3,5-triazine, quinone, anhydrous potassium carbonate are added into N-methylpyrrolidone with 22 times of the mass of 2,4,6-tris(4-fluorophenyl)-1,3,5-triazine, and toluene with 17 times of the mass of 2,4,6-tris(4-fluorophenyl)-1,3,5-triazine, under nitrogen protection, under the condition of stirring at 145℃, 250r / min, refluxing for 3.5h, increasing the temperature to 160℃ to evaporate toluene, increasing the temperature to 185℃, continuing to stir for 6.5h, cooling to room temperature, standing for 9h, centrifuging, washing with anhydrous ethanol for 4 times, drying at -80℃ under vacuum for 28h, to obtain triaryltriazine microspheres; the triaryltriazine microspheres, 3-mercapto-N,N,N-trimethylpropane-1-aminium chloride, azobisisobutyronitrile, N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:3.5:0.06:25, stirring at 75℃, 350r / min for 6.5h, suction filtration, washing with anhydrous ethanol for 4 times, drying at 55℃ under vacuum for 11h, to obtain functional triaryltriazine microspheres;

[0045] (4) 17.5 parts of modified polyvinyl alcohol, 49 parts of modified starch, 6.5 parts of polyacrylamide, 7.5 parts of functional triaryltriazine microspheres, and 1.25 parts of chloroplatinic acid are weighed according to the mass fraction; the modified polyvinyl alcohol, the modified starch, the polyacrylamide, the functional triaryltriazine microspheres, and the chloroplatinic acid are added into distilled water and mixed uniformly, and the viscosity is adjusted to 195mm 2 / s with distilled water, to obtain a composite slurry; the composite slurry is uniformly coated on base paper, the coating amount is 30g / m 2 , after coating, standing at 72.5℃ for 2.5h, drying at 55℃ under vacuum for 17h, slitting and rewinding, to obtain a gas stove battery pulp layer paper.

[0046] Example 3: A preparation method of a gas stove battery pulp layer paper, the preparation method of the gas stove battery pulp layer paper comprises the following preparation steps:

[0047] (1) 4-allyl aniline, 1-pyrazole methanol are added into N-methyl pyrrolidone with 16 times of the mass of 4-allyl aniline according to a molar ratio of 1:2, and 4-allyl aniline 0.08 times of the mass of tris(triphenylphosphine) ruthenium dichloride is added, stirring at 190℃, 300r / min for 20h, drying at 60℃ under vacuum for 10h, to prepare a double H-pyrazole methyl amine ligand; the double H-pyrazole methyl amine ligand, 1-vinyl-1,1,3,3-tetramethyldisiloxane, dodecyl phenol polyoxyethylene ether, sodium dodecyl sulfate, distilled water are mixed uniformly according to a mass ratio of 1:1:4:3:14, stirring at room temperature, 600r / min for 20min, to prepare a mixed reaction liquid; starch and distilled water are mixed uniformly according to a mass ratio of 1:22, stirring at 80℃ under nitrogen protection, 300r / min for 30min, cooling to 40℃, adding 0.12 times of the mass of starch ammonium persulfate and 0.12 times of the mass of starch sodium bisulfite, continuing to stir for 10min, adding the mixed reaction liquid at a speed of 15 times of the mass of starch within 20min, continuing to stir for 5h after the addition is completed, removing the solvent by rotary evaporation under reduced pressure, washing with anhydrous ethanol and distilled water for 5 times respectively, drying at 60℃ under vacuum for 10h, to prepare a modified starch;

[0048] (2) polyvinyl alcohol, urea, dicyandiamide, N,N-dimethylformamide are mixed uniformly according to a mass ratio of 1:2.5:1.6:9, stirring at 300r / min, heating to 130℃ at a heating rate of 5℃ / min, adding 1.3 times of the mass of polyvinyl alcohol 3-butene phosphonic acid monomethyl ester, stirring at 135℃ for 3h, dissolving the product in distilled water, precipitating with ethanol, repeating the dissolving-precipitating process for 6 times, drying at 60℃ under vacuum for 10h, to prepare a modified polyvinyl alcohol;

[0049] (3) 2,4,6-tris (4-fluorophenyl) -1,3,5-triazine, quinone, anhydrous potassium carbonate were added into N-methyl pyrrolidone with 24 times of the mass of 2,4,6-tris (4-fluorophenyl) -1,3,5-triazine, and toluene with 18 times of the mass of 2,4,6-tris (4-fluorophenyl) -1,3,5-triazine, in a mass ratio of 1:0.9:0.6, under the protection of nitrogen, refluxing for 3h at 150℃ with stirring at 300r / min, the toluene was evaporated by heating to 160℃, and the stirring was continued for 6h by heating to 190℃, cooled to room temperature, and then stood for 10h, centrifuged, washed with anhydrous ethanol for 5 times, and dried at-80℃ under vacuum for 30h to obtain triaryltriazine microspheres; the triaryltriazine microspheres, 3-mercapto-N, N, N-trimethylpropane-1- ammonium chloride, azobisisobutyronitrile, and N, N-dimethylformamide were mixed uniformly in a mass ratio of 1:4:0.07:26, and reacted for 6h at 80℃ with stirring at 400r / min, filtered, washed with anhydrous ethanol for 5 times, and dried at 60℃ under vacuum for 10h to obtain functional triaryltriazine microspheres;

[0050] (4) 18 parts of modified polyvinyl alcohol, 50 parts of modified starch, 7 parts of polyacrylamide, 8 parts of functional triaryltriazine microspheres, and 1.5 parts of chloroplatinic acid were weighed according to the mass fraction, and then added into distilled water to mix uniformly, and the viscosity was adjusted to 200mm 2 / s with distilled water to obtain a composite slurry; the composite slurry was uniformly coated on the base paper with a coating amount of 30g / m 2 , and then dried at 60℃ under vacuum for 16h after standing for 2h at 75℃ after coating, cut and rewound to obtain a gas stove battery pulp layer paper.

[0051] Comparative Example 1

[0052] The preparation method of the gas stove battery pulp layer paper of Comparative Example 1 is different from that of Example 2 in that step (1) is modified. Step (1) is modified as follows: 1-vinyl-1,1,3,3-tetramethyldisiloxane, dodecylphenol polyoxyethylene ether, sodium dodecyl sulfate, and distilled water are uniformly mixed in a mass ratio of 1:3.5:2.5:13, stirred at 550 r / min for 25 min at room temperature, and a mixed reaction solution is prepared; starch and distilled water are uniformly mixed in a mass ratio of 1:21, stirred at 250 r / min for 35 min at 78°C under nitrogen protection, cooled to 40°C, 0.11 times the mass of the starch of ammonium persulfate and 0.11 times the mass of the starch of sodium bisulfite are added, and stirring is continued for 12 min; the mixed reaction solution is added at a uniform speed within 20 min, and after the addition is completed, stirring is continued for 5.5 h; the solvent is removed by rotary evaporation under reduced pressure, washed with anhydrous ethanol and distilled water four times each, and dried at 55°C under vacuum for 11 h to prepare modified starch. The remaining steps are the same as in Example 2.

[0053] Comparative Example 2:

[0054] The preparation method of the gas stove battery pulp layer paper of Comparative Example 2 is different from that of Example 2 in that step (1) is modified. Step (1) is modified as follows: 4-allyl aniline and 1-pyrazole methanol are added to 15 times the mass of 4-allyl aniline of N-methyl pyrrolidone in a molar ratio of 1:2, 0.07 times the mass of 4-allyl aniline of tris(triphenylphosphine)ruthenium dichloride is added, stirred at 250 r / min for 22 h at 185°C, and dried at 55°C under vacuum for 11 h to prepare a double H-pyrazole methyl amine ligand; the double H-pyrazole methyl amine ligand, dodecylphenol polyoxyethylene ether, sodium dodecyl sulfate, and distilled water are uniformly mixed in a mass ratio of 1:3.5:2.5:13, stirred at 550 r / min for 25 min at room temperature, and a mixed reaction solution is prepared; starch and distilled water are uniformly mixed in a mass ratio of 1:21, stirred at 250 r / min for 35 min at 78°C under nitrogen protection, cooled to 40°C, 0.11 times the mass of the starch of ammonium persulfate and 0.11 times the mass of the starch of sodium bisulfite are added, and stirring is continued for 12 min; the mixed reaction solution is added at a uniform speed within 20 min, and after the addition is completed, stirring is continued for 5.5 h; the solvent is removed by rotary evaporation under reduced pressure, washed with anhydrous ethanol and distilled water four times each, and dried at 55°C under vacuum for 11 h to prepare modified starch. The remaining steps are the same as in Example 2.

[0055] Comparative Example 3:

[0056] The preparation method of the gas stove battery pulp paper in Comparative Example 3 differs from that in Example 2 in that step (2) is omitted, and step (4) is modified as follows: Weigh 17.5 parts of polyvinyl alcohol, 49 parts of modified starch, 6.5 parts of polyacrylamide, 7.5 parts of functional triaryltriazine microspheres, and 1.25 parts of chloroplatinic acid by mass; add polyvinyl alcohol, modified starch, polyacrylamide, functional triaryltriazine microspheres, and chloroplatinic acid to distilled water and mix evenly, and adjust the viscosity to 195 mm with distilled water. 2 / s, to obtain a composite slurry; the composite slurry is then uniformly coated onto the base paper, with a coating amount of 30g / m. 2 After coating, the mixture was left to stand at 72.5°C for 2.5 hours, then dried at 55°C for 17 hours under vacuum. The resulting paper was then slit and rewound to obtain the gas stove battery pulp layer paper. The remaining steps were the same as in Example 2.

[0057] Comparative Example 4:

[0058] The preparation method of the gas stove battery pulp paper in Comparative Example 4 differs from that in Example 2 in that step (3) is omitted, and step (4) is modified as follows: Weigh 17.5 parts of modified polyvinyl alcohol, 49 parts of modified starch, 6.5 parts of polyacrylamide, and 1.25 parts of chloroplatinic acid by mass; add the modified polyvinyl alcohol, modified starch, polyacrylamide, and chloroplatinic acid to distilled water and mix evenly, and adjust the viscosity to 195 mm with distilled water. 2 / s, to obtain a composite slurry; the composite slurry is then uniformly coated onto the base paper, with a coating amount of 30g / m. 2 After coating, the mixture was left to stand at 72.5°C for 2.5 hours, then dried at 55°C for 17 hours under vacuum. The resulting paper was then slit and rewound to obtain the gas stove battery pulp layer paper. The remaining steps were the same as in Example 2.

[0059] Test Example 1

[0060] Leakage prevention performance test

[0061] Test method: Using the examples and comparative examples as the pulp paper for carbon-zinc batteries, zinc-manganese batteries were assembled according to GB8897-2008-T, and the leakage resistance of the batteries was tested. The results are shown in Table 1.

[0062] Table 1

[0063] ;

[0064] A comparison of the experimental data from Examples 1-3 and Comparative Examples 1-4 in Table 1 reveals that the gas stove battery paste paper prepared by this invention has good leak-proof performance.

[0065] By comparison, the leakage prevention effect of examples 1-3 is better than that of comparative example 1, which shows that the double H-pyrazole methyl amine ligand is prepared by reacting 4-allyl aniline and 1-pyrazole methanol; the modified starch is prepared by grafting copolymerization of the double H-pyrazole methyl amine ligand and 1-vinyl-1,1,3,3-tetramethyl disiloxane on starch; the double H-pyrazole methyl amine ligand structure has strong coordination ability and can complex with zinc ions on the surface of the zinc negative electrode to form a protective layer, preventing further corrosion of the zinc negative electrode.

[0066] By comparison, the leakage prevention effect of examples 1-3 is better than that of comparative example 4, which shows that the triaryl s-triazine microspheres are prepared by reacting 2,4,6-tris(4-fluorophenyl)-1,3,5-triazine and cattail phenol; the carbon-carbon double bond on the triaryl s-triazine microspheres is reacted with the mercapto group on 3-mercapto-N,N,N-trimethylpropane-1-ammonium chloride to prepare functional triaryl s-triazine microspheres; the quaternary ammonium salt structure is grafted on the surface of the functional triaryl s-triazine microspheres; the positively charged quaternary ammonium salt structure can combine with the negatively charged zinc surface after corrosion, adsorb on the surface of the zinc negative electrode, delay the further corrosion of the zinc surface, and thus improve the leakage prevention performance of the battery.

[0067] Test of flame retardant performance

[0068] Test method: pour the composite slurry prepared by the examples and comparative examples into a polytetrafluoroethylene mold, stand at 70℃ for 3h, dry at 50℃ under vacuum for 18h, prepare a standard sample according to GB / T2406, and test the limiting oxygen index of the standard sample. The results are shown in Table 2.

[0069] Table 2

[0070] ;

[0071] From the experimental data comparison of examples 1-3 and comparative examples 1-4 in Table 2, it can be found that the gas stove battery layer paper prepared by the present application has good flame retardant performance.

[0072] By comparison, the limiting oxygen index of examples 1-3 is greater than that of comparative example 2, which shows that the modified starch is prepared by grafting copolymerization of the double H-pyrazole methyl amine ligand and 1-vinyl-1,1,3,3-tetramethyl disiloxane on starch; the siloxane structure is introduced into the modified starch; the introduction of the siloxane structure can improve the flame retardant of the slurry layer paper.

[0073] By comparison, the limiting oxygen index of examples 1-3 is greater than that of comparative example 3, which shows that the modified polyvinyl alcohol is prepared by reacting polyvinyl alcohol and 3-butene phosphonic acid monomethyl ester; part of the hydroxyl groups on the side chain of the polyvinyl alcohol molecule esterify with the phosphoric acid group of the 3-butene phosphonic acid monomethyl ester to introduce phosphorus element on the side chain of the modified polyvinyl alcohol molecule, and the introduction of the phosphorus element further improves the flame retardant performance of the sizing layer paper.

[0074] By comparison, the limiting oxygen index of examples 1-3 is greater than that of comparative example 4, which shows that the functional triaryl s-triazine microspheres contain a triaryl s-triazine structure and have excellent flame retardant performance, which can further improve the flame retardant performance of the sizing layer paper.

[0075] Test example 3

[0076] Test of high temperature resistance

[0077] Test method: the thermal gravimetric analyzer TGA / SDTA851 is used to analyze the thermal gravimetry of examples and comparative examples, and the test conditions are as follows: nitrogen atmosphere, flow rate 40 mL / min, temperature rising rate 10 ℃ / min, and temperature range 30-500 ℃. The results are shown in Table 3.

[0078] Table 3

[0079] ;

[0080] From the comparison of the experimental data of examples 1-3 and comparative examples 1-4 in Table 3, it can be found that the sizing layer paper for gas stove batteries prepared by the present application has good high temperature resistance.

[0081] By comparison, the high temperature resistance of examples 1-3 is greater than that of comparative example 2, which shows that the modified starch is prepared by graft copolymerization of the double H-pyrazole methyl amine ligand and 1-vinyl-1,1,3,3-tetramethyldisiloxane on the starch; the siloxane structure and Si-H are introduced on the modified starch; the introduction of the siloxane structure can improve the high temperature resistance of the sizing layer paper; the Si-H introduced on the modified starch can undergo a silicon hydrogen addition reaction with the carbon-carbon double bond introduced on the side chain of the modified polyvinyl alcohol to form a crosslinked structure, and the three-dimensional network structure formed by the crosslinking reaction limits the movement between the molecular chains, reduces the thermal degradation at high temperature, and further improves the high temperature resistance.

[0082] By comparison, the high temperature resistance of examples 1-3 is greater than that of comparative example 3, which shows that the modified polyvinyl alcohol is prepared by reacting polyvinyl alcohol and 3-butene phosphonic acid monomethyl ester; part of the hydroxyl groups on the side chain of the polyvinyl alcohol molecule esterify with the phosphoric acid group of the 3-butene phosphonic acid monomethyl ester to introduce carbon-carbon double bonds on the side chain of the modified polyvinyl alcohol molecule, and the carbon-carbon double bonds undergo an addition reaction with the Si-H bonds on the modified starch to form a three-dimensional crosslinked network structure, which improves the high temperature resistance of the sizing layer paper.

[0083] By comparison, the high temperature resistance of Examples 1-3 is greater than that of Comparative Example 4, indicating that the triaryltriazine microspheres prepared by reacting 2,4,6-tris(4-fluorophenyl)-1,3,5-triazine and candelilla phenol contain triaryltriazine structures and have excellent high temperature resistance, which can further improve the high temperature resistance of the pulp layer paper.

[0084] Test Example 4

[0085] Test of mechanical strength

[0086] Test method: pour the composite slurry prepared from the examples and comparative examples into a polytetrafluoroethylene mold, stand at 70°C for 3h, dry at 50°C under vacuum for 18h, prepare standard samples according to GB / T1040.3, and test the tensile strength of the standard samples at a tensile rate of 300mm / min. The results are shown in Table 4.

[0087] Table 4

[0088] ;

[0089] From the experimental data comparison of Examples 1-3 and Comparative Examples 1-4 in Table 4, it can be found that the gas stove battery pulp layer paper prepared by the present application has good mechanical strength.

[0090] By comparison, the tensile strength of Examples 1-3 is greater than that of Comparative Example 2, indicating that the modified starch is prepared by graft copolymerization of the bis-H-pyrazole methyl amine ligand and 1-vinyl-1,1,3,3-tetramethyldisiloxane on starch; Si-H is introduced on the modified starch; the Si-H introduced on the modified starch can undergo a silicon hydrogen addition reaction with the carbon-carbon double bond introduced on the modified polyvinyl alcohol molecular side chain to form a crosslinked structure, and the crosslinking reaction forms a three-dimensional network structure that limits the movement between molecular chains, thereby improving the mechanical strength of the pulp layer paper material.

[0091] By comparison, the tensile strength of Examples 1-3 is greater than that of Comparative Example 3, indicating that the modified polyvinyl alcohol is prepared by reacting polyvinyl alcohol and 3-butene phosphonic acid monomethyl ester; part of the hydroxyl groups on the polyvinyl alcohol molecular side chain undergo esterification with the phosphoric acid group of 3-butene phosphonic acid monomethyl ester, introducing a carbon-carbon double bond on the modified polyvinyl alcohol molecular side chain, and the carbon-carbon double bond undergoes an addition reaction with the Si-H bond on the modified starch to form a three-dimensional crosslinked network structure, thereby improving the mechanical strength of the pulp layer paper.

[0092] The above detailed description of the specific embodiments of the present application has been given to understand the purpose, technical solutions and beneficial effects of the present application. It should be understood that the above description is only a specific embodiment of the present application and is not used to limit the protection scope of the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A paper for a battery of a gas stove, characterized in that, The gas stove battery pulp layer paper comprises a base paper and a coating layer coated on the base paper; The coating layer is composed of 17-18 parts of modified polyvinyl alcohol, 48-50 parts of modified starch, 6-7 parts of polyacrylamide, 7-8 parts of functional triaryl s-triazine microspheres, and 1-1.5 parts of chloroplatinic acid; The modified polyvinyl alcohol is prepared by reacting polyvinyl alcohol and 3-butene phosphonic acid monomethyl ester; The modified starch is prepared by graft copolymerization of double H-pyrazole methyl amine ligand and 1-vinyl-1,1,3,3-tetramethyl disiloxane on starch; The double H-pyrazole methyl amine ligand is prepared by reacting 4-allyl aniline and 1-pyrazole methanol; The functional triaryl s-triazine microspheres are prepared by reacting triaryl s-triazine microspheres and 3-mercapto-N,N,N-trimethyl propane-1-ammonium chloride; The triaryl s-triazine microspheres are prepared by reacting 2,4,6-tris(4-fluorophenyl)-1,3,5-triazine and quercitol.

2. A method for producing a battery jelly paper for a gas stove, characterized by, The preparation method of the gas stove battery pulp layer paper comprises the following preparation steps: (1) uniformly mix starch and distilled water, stir at 76-80°C under nitrogen protection for 30-40 min, cool to 40°C, add ammonium persulfate and sodium bisulfite, continue to stir for 10-14 min, uniformly drop the mixed reaction liquid within 20 min, continue to stir for 5-6 h after dropping, and prepare modified starch; (2) uniformly mix polyvinyl alcohol, urea, dicyandiamide and N,N-dimethylformamide, heat to 130°C, add 3-butene phosphonic acid monomethyl ester, react at 130-135°C for 3-4 h, and prepare modified polyvinyl alcohol; (3) uniformly mix triaryl s-triazine microspheres, 3-mercapto-N,N,N-trimethyl propane-1-ammonium chloride, azobisisobutyronitrile and N,N-dimethylformamide, react at 70-80°C for 6-7 h, and prepare functional triaryl s-triazine microspheres; (4) Modified polyvinyl alcohol, modified starch, polyacrylamide, functional triarylimidazole microspheres, chloroplatinic acid are added to distilled water and mixed uniformly, and the viscosity is adjusted to 190~200mm 2 / s with distilled water to prepare a composite slurry; the composite slurry is uniformly coated on the base paper, and after coating, it is placed at 70~75℃ for 2~3h, dried, cut and rewound to prepare a gas stove battery pulp layer paper.

3. The method of claim 2, wherein the paper is a battery separator paper. The preparation method of the mixed reaction liquid in step (1) is as follows: uniformly mix double H-pyrazole methyl amine ligand, 1-vinyl-1,1,3,3-tetramethyl disiloxane, dodecylphenol polyoxyethylene ether, sodium dodecyl sulfate and distilled water in a mass ratio of 1:1:(3-4):(2-3):(12-14), stir at room temperature for 20-30 min, and prepare the mixed reaction liquid.

4. The method of claim 3, wherein the paper is a battery separator paper. The preparation method of the double H-pyrazole methyl amine ligand is as follows: add 4-allyl aniline and 1-pyrazole methanol in a molar ratio of 1:2 into N-methyl pyrrolidone, add 0.06-0.08 times the mass of 4-allyl aniline of tris(triphenylphosphine)ruthenium dichloride, react at 180-190°C for 20-24 h, and vacuum dry to prepare the double H-pyrazole methyl amine ligand.

5. The method of claim 2, wherein the paper is a battery separator paper. The mass ratio of polyvinyl alcohol, urea, dicyandiamide and N,N-dimethylformamide in step (2) is 1:(2.4-2.5):(1.5-1.6):(8-9).

6. The method of producing a battery jelly-roll paper for a gas stove according to claim 2, wherein The amount of 3-butene phosphonic acid monomethyl ester in step (2) is 1.2-1.3 times the mass of polyvinyl alcohol.

7. The method of producing a battery jelly-roll paper for a gas stove according to claim 2, wherein The preparation method of the triaryltriazine microspheres in step (3) is as follows: 2,4,6-tris(4-fluorophenyl)-1,3,5-triazine, quinone, and anhydrous potassium carbonate are added into N-methylpyrrolidone at a mass ratio of 1:(0.8-0.9):(0.5-0.6), toluene is added, under the protection of nitrogen, under the condition of stirring at 200-300 r / min, refluxing at 140-150 ℃ for 3-4 h, evaporating toluene by heating to 160 ℃, continuing to stir and react for 6-7 h by heating to 180-190 ℃, and the triaryltriazine microspheres are prepared.

8. The method of producing a battery jelly-roll paper for a gas stove according to claim 2, wherein The dosages of the modified polyvinyl alcohol, modified starch, polyacrylamide, functional triaryltriazine microspheres, and chloroplatinic acid in step (4) are as follows: the modified polyvinyl alcohol is 17-18 parts, the modified starch is 48-50 parts, the polyacrylamide is 6-7 parts, the functional triaryltriazine microspheres are 7-8 parts, and the chloroplatinic acid is 1-1.5 parts.

9. The method of producing a battery jelly-roll paper for a gas stove according to claim 2, wherein The coating amount of the composite slurry on the base paper in step (4) is 30 g / m 2 .

Citation Information

Patent Citations

  • Coated paper for improving leakage resistance of carbon battery and preparation method of coated paper

    CN113201971A

  • Low-temperature-resistant zero-formaldehyde water-based adhesive and preparation process thereof

    CN116144296A